Pengaruh Implementasi Karunia Bernubuat dan Karunia Bahasa Lidah Terhadap Perubahan Kualitas Karakter Jemaat”, Penelitian pada Gereja Bethel Indonesia di Wilayah Kelurahan Kombos Timur Manado - Yonggi Sampelan (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2021)
One of the goals of evangelism is to change the character of the congregation that is discipled through evangelism. To achieve a significant change in character, many supporting/pushing factors are needed. Researchers in the initial observation found that one of the factors was the gifts of the Holy Spirit. The researcher then chooses the gift of prophecy and the gift of tongues, apart from being unique from other gifts, these gifts are more evenly distributed in each congregation that will be studied by the researcher. This was obtained from a brief interview with the pastor of each congregation. The gift of prophecy is essentially the gift of receiving a message/inspiration from God to be conveyed to oneself or others, in this case the congregation concerned. Then the gift of tongues is essentially the ability to speak in a foreign language that neither the speaker nor the listener understands, except for the type of xenolalia. So that the gift of interpreting/translating tongues is also needed, unless it is used as a sign of the fullness of the Spirit, which is generally for the personal needs concerned. The problem in this research is whether there is an effect of implementing the gift of prophecy and the gift of tongues on the transformation of the character quality of the Indonesian Bethel Church congregation in the East Kombos region, Manado. Then find out how big the influence is. The population in this study was the entire Indonesian Bethel Church congregation in the East Kombos area, Manado, totaling 298 people from 7 congregations. The technique used in the sampling of this research is to use proportional random sampling. To determine the number of samples to be taken in this study, researchers used the Slovin formula so that 75 people were obtained who would be used as research samples. The variables in this study were the gift of prophecy and the gift of tongues as the independent variable and the quality of character as the dependent variable. The data retrieval technique used in this study is to use a questionnaire (questionnaire) and documentation techniques. The test results using the SPSS program are known to have a significance value for the motivation variable of 0.014 so it can be concluded that there is an influence between the gift of prophecy on the transformation of the quality of the character of the GBI congregation in the East Kombos region, or Ha is accepted. For the gift of tongues variable, it is known that the significance value is 0.019, so it can be concluded that there is an influence between the implementation of the gift of tongues on the transformation of the quality of the character of the GBI congregation in East Kombos, Manado, or Ha received. The results of the simultaneous test are known to have a significance value of 0.000 so that it can be concluded that there is an influence between the implementation of the gift of prophecy and the gift of tongues on the transformation of the character quality of the GBI congregation in East Kombos, Manado, or Ha received. The results of the calculation of the coefficient of determination are known that the magnitude of the influence between X1 and X2 on Y is 0.204 or 20.4%. While the remaining 79.6% is influenced by other factors not disclosed in this study.